2016
DOI: 10.1126/science.aaf7671
|View full text |Cite
|
Sign up to set email alerts
|

The broad footprint of climate change from genes to biomes to people

Abstract: Most ecological processes now show responses to anthropogenic climate change. In terrestrial, freshwater, and marine ecosystems, species are changing genetically, physiologically, morphologically, and phenologically and are shifting their distributions, which affects food webs and results in new interactions. Disruptions scale from the gene to the ecosystem and have documented consequences for people, including unpredictable fisheries and crop yields, loss of genetic diversity in wild crop varieties, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
763
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,031 publications
(778 citation statements)
references
References 294 publications
6
763
0
9
Order By: Relevance
“…According to the Millennium Ecosystem Assessment (MEA 2005), land use change has had the highest impact of all pressures on biodiversity. Even so, some studies indicate that climate change may be the biggest pressure, and climate effects are currently significant and forecasted to be an emerging major threat (Scheffers et al 2016). Some studies have suggested that over the next few decades, climate change could surpass land use change as the greatest global threat to plant life (Leadley et al 2010;Bellard et al 2012).…”
Section: Application Of Metrics To Human-induced Pressuresmentioning
confidence: 99%
“…According to the Millennium Ecosystem Assessment (MEA 2005), land use change has had the highest impact of all pressures on biodiversity. Even so, some studies indicate that climate change may be the biggest pressure, and climate effects are currently significant and forecasted to be an emerging major threat (Scheffers et al 2016). Some studies have suggested that over the next few decades, climate change could surpass land use change as the greatest global threat to plant life (Leadley et al 2010;Bellard et al 2012).…”
Section: Application Of Metrics To Human-induced Pressuresmentioning
confidence: 99%
“…Sus efectos recaerán no solo sobre el medio físico, sino también sobre la biodiversidad pudiendo provocar pérdidas de diversidad y funcionalidad biológica; por consiguiente, irremediablemente tendrán consecuencias en el bienestar humano (Scheffers et al 2016).…”
Section: Cambio Climático: Vulnerabilidad De Los Humedales De Alturaunclassified
“…monitoreo de la respuesta de los humedales a variaciones en el clima). Estas observaciones permitirían identificar los mecanismos por los que se manifiesta, y modelarlos matemáticamente para predecir sus efectos frente a escenarios futuros de cambio climático (Scheffers et al 2016). Estas predicciones a su vez permitirían diseñar medidas de mitigación y adaptación a dichos efectos, e informar a la toma de decisiones para su correcta planificación y gestión.…”
Section: Cómo Esclarecer Los Efectos Del Cambio Climáticounclassified
“…El Stockholm Resilience Centre ha desarrollado el concepto de las fronteras planetarias y según su análisis hay tres de nueve procesos (cambio climático, acidificación de los océanos y agotamiento del ozono estratosférico) que ya han alcanzado el punto de inflexión (Scheffers et al, 2016).…”
Section: Introductionunclassified